Destabilizing Capital Flows amid Global Inflation - Bengui, Julien; Coulibaly, Louphou (Review of Economic Studies, 2026)
Abstract Over the latest monetary policy tightening cycle, capital has been flowing from low-inflation countries to high-inflation countries. This pattern of capital flows is consistent with the predictions of an open-economy model with nominal rigidities where cost-push shocks generate an inflationary episode and capital flows freely across countries. Yet, by raising demand for domestic non-tradable goods and services, capital inflows cause unwelcome upward pressure on firms’ costs in countries most severely hit by these shocks. We find that a reverse pattern of capital flows would have improved the output-inflation trade-off globally, hence requiring a less aggressive monetary tightening in the most severely hit countries and delivering overall welfare gains.